Spinal oncologic paraparesis: Analysis of neurological and surgical outcomes in patients with intramedullary, extramedullary, and extradural tumors - Alhalabi, Obada T.; Heene, Stefan; Landré, Vincent; Neumann, Jan-Oliver; Scherer, Moritz; Ishak, Basem; Kiening, Karl; Zweckberger, Klaus; Unterberg, Andreas W.; Younsi, Alexander (Frontiers in Oncology, 2023)
Objectives: Paraparesis due to oncologic lesions of the spine warrants swift neurosurgical intervention to prevent permanent disability and hence maintain independence of affected patients. Clinical parameters that predict a favorable outcome after surgical intervention could aid decision-making in emergency situations. Methods: Patients who underwent surgical intervention for paraparesis (grade of muscle strength <5 according to the British Medical Research Council grading system) secondary to spinal neoplasms between 2006 and 2020 were included in a single-center retrospective analysis. Pre- and postoperative clinical data were collected. The neurological status was assessed using the modified McCormick Disability Scale (mMcC) Score. In a univariate analysis, patients with favorable (discharge mMcC improved or stable at <3) and non-favorable outcome (discharge mMcC deteriorated or stable at >2) and different tumor anatomical compartments were statistically compared. Results: 117 patients with oncologic paraparesis pertaining to intramedullary lesions (n=17, 15%), intradural extramedullary (n=24, 21%) and extradural lesions (n=76, 65%) with a mean age of 65.3±14.6 years were included in the analysis. Thoracic tumors were the most common (77%), followed by lumbar and cervical tumors (13% and 12%, respectively). Surgery was performed within a mean of 3660 hours of admission across all tumors and included decompression over a median of 2 segments (IQR:1-3) and mostly subtotal tumor resection (n=83, 71%). Surgical and medical complications were documented in 9% (n=11) and 7% (n=8) of cases, respectively. The median hospital length-of-stay was 9 (7-13) days. Upon discharge, the median mMcC score had improved from 3 to 2 (p<0.0001). At last follow-up (median 180; IQR 51-1080 days), patients showed an improvement in their mean Karnofsky Performance Score (KPS) from 51.718.8% to 65.320.4% (p<0.001). Localization in the intramedullary compartment, a high preoperative mMcC score, in addition to bladder and bowel dysfunction were associated with a non-favorable outcome (p<0.001). Conclusion: The data presented on patients with spinal oncologic paraparesis provide a risk-benefit narrative that favors surgical intervention across all etiologies. At the same time, they outline clinical factors that confer a less-favorable outcome like intramedullary tumor localization, a high McCormick score and/or bladder and bowel abnormalities at admission.